2008
DOI: 10.1007/s11412-008-9050-8
|View full text |Cite
|
Sign up to set email alerts
|

The right tool for the wrong task? Match and mismatch between first and second stimulus in double stimulation

Abstract: Using Vygotsky's notion of double stimulation as an analytical tool, we discuss the complex relationship between tasks, tools, and agency in CSCL environments. Empirically we examine how learners in a Norwegian senior high school class learning English as a foreign language approach and respond to an open-ended and collectively oriented task using a wiki. Our findings show that collectively oriented knowledge and language production takes place locally in small groups as well as in the larger collective of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 28 publications
0
43
0
1
Order By: Relevance
“…In particular, it appears possible -on the basis of the evidence of the cases reported in the present paper -that digital tools used in the classroom might be seen as possessing certain properties that render them as particularly effective in filling the space between abstract and concrete manifestations of cognitive activity such as comprehension. Digital tools have transformed the subject matter and ways of communication (Blikstad-Balas, 2012;Säljö, 2010;Schofield, 2014); as a result, students meet multimodal hypertexts, enabling them to read in various ways and communicate across time and space (Lund, Furberg, Bakken, & Engelien, 2014;Lund & Rasmussen, 2008). These new modes of reading require students to use reading strategies in new ways, or to develop new strategies (Brevik, 2015;Frønes, Narvhus, & Aasebø, 2013;Roe, 2014).…”
Section: The Context Of the Studymentioning
confidence: 99%
“…In particular, it appears possible -on the basis of the evidence of the cases reported in the present paper -that digital tools used in the classroom might be seen as possessing certain properties that render them as particularly effective in filling the space between abstract and concrete manifestations of cognitive activity such as comprehension. Digital tools have transformed the subject matter and ways of communication (Blikstad-Balas, 2012;Säljö, 2010;Schofield, 2014); as a result, students meet multimodal hypertexts, enabling them to read in various ways and communicate across time and space (Lund, Furberg, Bakken, & Engelien, 2014;Lund & Rasmussen, 2008). These new modes of reading require students to use reading strategies in new ways, or to develop new strategies (Brevik, 2015;Frønes, Narvhus, & Aasebø, 2013;Roe, 2014).…”
Section: The Context Of the Studymentioning
confidence: 99%
“…For instance, Sykes, Oskoz, and Thorne (2008) introduced wikis as a means of collaborative content building and dissemination of information, and wikis were described as a specific environment that utilizes collaborative tools in a study focused on the implementation of active and collaborative practices in information and communication technology classrooms. Lund and Rasmussen (2008) empirically examined how learners of senior high school English as a foreign language (EFL) approached and responded to an open-ended and collectively oriented task using a wiki and found that wikis helped learners to sustain strategies with many characteristics of collective production. They also noted that wikis can foster collective awareness.…”
Section: Research On Wikis As a Tool For Language Learningmentioning
confidence: 99%
“…At the same time, computer-supported collaborative learning (CSCL) is being applied to second language learning (Ge, 2011;Lund & Rasmussen, 2008;Stahl, 2006). Virtual environments that provide chat functions and avatar interaction in 3D environments have been studied as a tool for facilitating collaborative learning (e.g., Baydas et al, 2015;Molenaar et al, 2011;Silseth, 2011;Prensky, 2001).…”
Section: English Immersed Education and Computer-supported Collaboratmentioning
confidence: 99%